Measures and Values. - Chambers, R. J. (The Accounting Review, 1968)
Abstract In this article the author comments on the critical review of one of his articles by George J. Staubus. He states that he has been at some pains to point out that more than one kind of information is necessary to every choice, and that monetary magnitudes of quite different types are necessary. According to him there are the monetary magnitudes of the assets and equities a firm has at any time. Then there are the monetary magnitudes obtained by discounting the expected cash inflows and outflows from proceeding in the same way as up to the point of choice, and from every alternative course which seems to be feasible at the point of choice. There is no problem of dealing in money and goods in a deliberate and informed manner for which both types of magnitudes are not necessary. Among the things an investor might expect to know are the rates of return earned by the two companies, their liquidities or degrees of solvency, and their leverages. The author concludes that for any choice between holding an asset and acquiring another, whether by managers or investors, current cash equivalents of the assets held enter into the statement of conditions for informed choice.